2017
DOI: 10.1111/bcpt.12851
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Long Non‐Coding RNA Growth Arrest‐Specific 5 in Glucocorticoid Response in Children with Inflammatory Bowel Disease

Abstract: Glucocorticoids (GCs) are widely employed in inflammatory, autoimmune and neoplastic diseases, and, despite the introduction of novel therapies, remain the first-line treatment for inducing remission in inflammatory bowel disease (IBD). Given the high incidence of suboptimal response, associated with a significant number of side-effects, that are particularly severe in paediatric patients, the identification of subjects that are most likely to respond poorly to GCs is extremely important. Recent evidence sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 27 publications
3
29
0
Order By: Relevance
“…In a recent study using both cell lines and IBD patient samples, an increased level of lncRNA GAS5 was identified after treatment with glucocorticoids (GCs). A significant increase in the level of GAS5 was shown to be the rate-limiting factor in the remission of at least 20% of IBD patients showing resistance to GC treatment 72 . GCs are one of the first line medications in the treatment of both main types of IBD.…”
Section: Gas5mentioning
confidence: 97%
See 1 more Smart Citation
“…In a recent study using both cell lines and IBD patient samples, an increased level of lncRNA GAS5 was identified after treatment with glucocorticoids (GCs). A significant increase in the level of GAS5 was shown to be the rate-limiting factor in the remission of at least 20% of IBD patients showing resistance to GC treatment 72 . GCs are one of the first line medications in the treatment of both main types of IBD.…”
Section: Gas5mentioning
confidence: 97%
“…It has been shown that GAS5 is differentially expressed in cell lines before and after methylprednisolone treatment and is positively correlated with drug resistance. A 4-week treatment of 19 pediatric IBD patients who were categorized as steroid-resistant (SR), steroid-sensitive (SS), or steroid-dependent (SD) showed that SR and SD patients had higher levels of GAS5 expression than the SS group 72 . As a result of these findings, the authors suggest that GAS5 expression can be considered a candidate marker of GC resistance.…”
Section: Gas5mentioning
confidence: 99%
“…In poor responders to GCs, the levels of lncRNA growth arrest-specific 5 (GAS5) were higher than those in good responders; therefore, GAS5 may be associated with GCs resistance 123,124 . A later study demonstrated that the expression of GAS5 differed between GCssensitive and GCs-resistant cells, and GAS5 is positively correlated with GCs resistance in children with IBD 125 . Additionally, endogenous GAS5 affects GCs effectiveness, likely because it accumulates in the cytoplasm and plays a role at the post-transcriptional level 125 .…”
Section: Lncrnas As Predictors Of Therapeutic Response In Ibdmentioning
confidence: 96%
“…This GAS5-dependent GC inhibitory pathway appears to also be active in some immune cells [113,114]. Although there are no crystal structures of GR bound to RNA, such structures have been modeled [110].…”
Section: Non-genomic Mechanisms Of Gene Regulation By Glucocorticoidsmentioning
confidence: 99%